Report of the Working Group of Sub-Committee of the National Development Council (NDC) on Agriculture and Related Issues on Dryland / Rainfed Farming System Including Regeneration of Degraded / Waste Land, Watershed Development Programme - Planning Commission (Planning Commission, 2005)
Food grain production in the country accrues from approximately 142 million hectares of cultivated land. Of this, 40 per cent is irrigated and accounts for 55 per cent of production. The remaining 85 million hectares are rainfed and contribute 45 per cent to total agriculture production. The Green Revolution was the principal instrument in imparting dynamism to agricultural growth in the post Independence era in India. Modern agricultural technology developed and extended since independence has contributed to unprecedented agricultural growth in the country. Green Revolution mainly concentrated in the irrigated areas and therefore, by and large bypassed the rainfed regions. Rainfed agriculture is complex, diverse and risk prone and is characterized by low levels of agriculture productivity and low input usage. Dependence on rainfall makes crops production considerably unstable in rainfed areas which are the habitat of the bulk of rural poor in the country.
Planning Commission Government of India
Planning Commission Government of India